Continuous Glucose Monitoring as a Valuable Tool in the Early Detection of Diabetes Related to Cystic Fibrosis - Gojsina, Bojana; Minic, Predrag; Todorovic, Sladjana; Soldatovic, Ivan; Sovtic, Aleksandar (Frontiers in Pediatrics, 2021)
Aims: We evaluated the impact of cystic fibrosis-related diabetes (CFRD) on lung disease and nutritional status. Study design: The retrospective cohort study evaluated the subjects’ medical records from 2004 to 2019. All participants older than ten years diagnosed by a 30-minutely sampled OGTT formed OGTT-CFRD subgroup. The participants diagnosed with CGM (at least two peaks above 11.1mmol/l and more than 10% of recorded time above 7.8mmol/l) formed a CFRD-CGM subgroup. The participants without CFRD formed a non-CFRD group. The longitudinal follow-up was made two years before and three years after insulin therapy initiation. Results: Of 144 participants included, aged 10 to 55 years (44% males), 28 (19.4%) had CFRD. The HbA1c was significantly lower in the CGM-CFRD in comparison to the OGTT-CFRD subgroup (5.9±0.62% and 7.3±1.7% respectfully; p=0.04). Subjects with CFRD were malnourished in comparison to non-CFRD, with significant improvements with insulin replacement therapy in regard to BMI Z score (-1.4±1.3 vs. -0.5±1.2, p=0.04)and pulmonary exacerbation score (p=0.02). In OGTT-CFRD subgroup there is an increase in FEV1 (62.7±26.3% to 65.1±21.7%, p=0.7) and decrease in FVC (from 76.4±24.2% to 71.2±20%, p=0.003) from diagnosis to second year of follow-up. In CGM-CFRD subgroup there was a decrease in FEV1 (from 58.2±28.2% to 52.8±25.9%, p=0.2) and FVC values (from 72.4±26.5% to 67.4±29.1%, p=0.08).Chronic P.aeruginosa infection was more prevalent in the CFRD group (p=0.003). Conclusion: CGM is a useful tool for insight of glucose impairment and diagnosis of CFRD. Early recognition of CFRD and therapeutic intervention has favorable effects on clinical course of the disease.